Exploration of different solid variants of the anticancer medication Panobinostat (PNB) with improved physicochemical attributes - Kenguva, Gowtham; Giri, Lopamudra; Rout, Smruti Rekha; Acharya, Achyuta Nanda; Dandela, Rambabu (Journal of Molecular Structure, 2023)
Panobinostat (PNB), is a medication used for the treatment of multiple myeloma. It is a BCS Class II drug with strong permeability and poor solubility. Therefore, it is highly desirable to investigate novel PNB variants with improved physiochemical properties. In this regard, several solid forms of PNB have been produced employing mechanochemistry and solution crystallisation techniques using a variety of GRAS (Generally Recognized as Safe) salt formers, notably oxalic acid (OA), fumaric acid (FA), maleic acid (MA), and succinic acid (SA). Powder X-Ray Diffraction (PXRD), Single Crystal X-Ray Diffraction (SCXRD), and thermal analysis such as Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to characterize all the synthesised molecular adducts. Hirshfeld surfaces and fingerprint plots demonstrate that the molecular entities are stabilized by O & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;C and H & BULL;& BULL;& BULL;H intermolecular interactions. Moreover, the solubility of parent PNB and its molecular adducts in pH 1.2/pH 6.8 was evaluated at room temperature. In every instance, an increase in the solubility of molecular salts relative to the parent medication is seen, notably PNB.MA exhibits enhanced solubility of 0.294 mg/ml, a 73fold increase over the parent PNB. Furthermore, it is observed that this upsurge in solubility of all the forms is static at pH 1.2. A thorough analysis of the recovered residue after solubility showed that most of the molecular adducts were stable at pH 6.8 and did not display any phase change or dissociation (with the exception of PNB.MA), but at pH 1.2 they transferred into a new stable form and extensive analysis confirmed that it converted into PNB.Cl salt. To the best of our knowledge, this is the first report on novel solid forms of PNB with enhanced physicochemical properties which implies that the obtained PNB molecular adduct may help in the development of improved PNB formulations.
Keywords: Hydrogen bond; Molecular adducts; solubility; Solvates